Evaluation of serum Cystatin C as a reliable marker of renal dysfunction in chronic liver disease - Bibi, Anila; Farhan, Muhammad; Rehman, Sadia; Kumar, Santosh; Junejo, Abdul Manan; Zehra, Afsheen (Journal of the Pakistan Medical Association, 2026)
Objective: To compare the reliability of serum cystatin C and serum creatinine in assessing renal dysfunction among chronic liver disease patients. Method: The cross-sectional study was conducted from May 1, 2023, to January 30, 2024, at the Jinnah Postgraduate Medical Centre, Karachi, in collaboration with the University of Karachi and the Bahria University of Health Sciences, Karachi. The sample comprised healthy controls in group A, chronic liver disease patients Child-Pugh class A in group B, chronic liver disease Child-Pugh class B in group C, and chronic liver disease Child-Pugh class C in group D. Baseline demographic data was collected, and blood samples were analysed for liver and renal function tests. Serum cystatin C and creatinine levels were measured, and the ratio between the two was calculated to assess renal impairment. Data was analysed using SPSS 25. Results: Of the 200 participants, 108(54%) were females and 92(46%) were males. Mean serum cystatin C levels increased significantly across Child-Pugh classes (0.7mg/L in controls vs 1.13mg/L in class A, 1.46mg/L in class B, and 1.53mg/L in class C; p<0.01). Serum creatinine levels also showed an increase (0.69mg/dL in controls vs 0.90mg/dL, 0.97mg/dL, and 0.99mg/dL respectively; p<0.01), though the rise was less consistent across patient groups. Blood urea nitrogen levels demonstrated a marked progressive increase from control to class C (p<0.01). Renal impairment was significantly associated with worsening Child-Pugh class (p<0.01). Conclusion: Serum cystatin C was a more reliable marker of renal impairment than serum creatinine in chronic liver disease and correlated with disease severity, supporting its use in early detection. Key Words: Cystatin C, Creatinine, Liver disease, Renal insufficiency, Glomerular filtration rate.